2009
DOI: 10.1016/j.bbadis.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Iron speciation study in Hfe knockout mice tissues: Magnetic and ultrastructural characterisation

Abstract: Liver, spleen and heart tissues of DBA/2 Hfe knockout mice have been characterised by low temperature AC magnetic susceptibility measurements together with Transmission Electron Microscopy (TEM) and Selected Area Electron Diffraction in order to investigate the chemical iron speciation in a murine model of iron overload diseases. With emphasis on ferritin-like species, the temperature dependent in-phase and out-of-phase susceptibility profiles agree with the elemental analysis in that, in this model, iron accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
3
17
1
1
Order By: Relevance
“…Goethite-like iron particles similar to those observed in these fossil soft tissues have been identified in modern tissues and are possibly derived from HB through formation of ferritin protein-caged iron biominerals [44,[75][76][77][78][79] during degradation. Ferritins are stable proteins that retain activity post-mortem.…”
Section: Discussionmentioning
confidence: 93%
“…Goethite-like iron particles similar to those observed in these fossil soft tissues have been identified in modern tissues and are possibly derived from HB through formation of ferritin protein-caged iron biominerals [44,[75][76][77][78][79] during degradation. Ferritins are stable proteins that retain activity post-mortem.…”
Section: Discussionmentioning
confidence: 93%
“…The complexity of the hysteresis loops (especially for class III sample) may be caused by a multicomponent composition of the samples containing deposits of several magnetic and non-magnetic iron oxides (α-Fe 2 O 3 , γ-Fe 2 O 3 , Fe 3 O 4 ) of different size, shape, and count [34].…”
Section: Discussionmentioning
confidence: 99%
“…46 Mouse serum ferritin contains a measurable but low amount of iron. This low iron content and the extreme similarity of the serum and liver ferritin cores, assessed by TEM and AC susceptometry, 30 suggest that the few serum ferritin cages that contain an H-subunit accumulate iron as ferrihydrite as well. The fact that the average iron content of liver ferritin is much higher than the average iron found in serum ferritin, despite the fact that the core sizes are similar, supports the notion that most ferritin in serum is apoferritin.…”
Section: Iron In Serum Ferritinmentioning
confidence: 99%
“…4,29 To broaden the knowledge of serum ferritin to other species and conditions, we characterized mouse serum ferritin in control mice and chemically iron-loaded animals. We used mass spectrometry (MS), transmission electron microscopy (TEM), alternating current (AC) magnetic susceptometry for ferritin-iron core analysis, 30 Western blotting, and glycosylation analysis, along with additional sensitive assays for iron determination, to characterize serum ferritin and to gain further insight into mechanisms of secretion and the possible role of serum ferritin in reallocation of body iron stores. We concluded that murine serum ferritin is mainly secreted by macrophages through a nonclassical secretion process involving secretory lysosomes and not the ER.…”
mentioning
confidence: 99%